Dynamic analysis of the efficiency of research and development systems of South-European countries - Mimović, Predrag; Krstić, Ana; Jakšić, Milena (Yugoslav Journal of Operations Research, 2019)
The non-parametric deterministic procedure of Data Envelopment Analysis (DEA) to measure and compare relative efficiency of research and development (R/D) activities in nine South-European countries in the period 2007-2016 is applied in this paper. To that end, we made a corresponding DEA model with nine decision-making units, two inputs and two outputs, selected by correlation analysis. The obtained results, i.e., relative R/D efficiency, were subject to correlation analysis in the context of the achieved average gross domestic product growth rate of the observed decision-making units, which showed that there was no strong correlation between those two variables at the level of the observed national economies.